The Influence of Fintech and Financial Literacy on Personal Financial Behavior of Medan State University Students - Situmeang, Fery Wahyu; Trianingsih, Hoza; Jessica, Jessica (Asosiasi Dosen Akuntansi Indonesia, 2023)
A situation where the whole world is attacked by a deadly virus, Covid19. Making the earth's population experience difficulties, both the community and the government. Especially Indonesia, one of the developing countries, felt a huge impact. Starting from threatened health and damaged economy. Because of this, every government must turn their heads to determine policies. The policies issued must be able to reduce and even stop the spread of the Covid19 virus. The government generally makes lockdown, online school, and WFH (Work from Home) policies. The author conducts research aimed at finding out how much influence public trust has on the Medan city government's policy in dealing with Covid 19 and this research is a follow-up research to previous research. The research was conducted using a quantitative method approach, the authors distributed questionnaires given to 30 people and processed the data using SPSS26. Based on the answers given by students as respondents, it shows their distrust of the policies that have been issued during the Covid-19 pandemic. In other words, the effect of public trust in the Medan City government policy is negative.